'What can I do'? Child welfare workers' perceptions of what they can do to address poverty. Issue 2 (3rd July 2017) - Carlson, Juliana
ABSTRACT: Within the field of child welfare, critical questions have been posed about the intersecting issues of child maltreatment and poverty. The study of the quality and nature of this intersection has continued relevance in light of evidence showing the increased likelihood of maltreatment of children living in poverty. Although child welfare workers interact directly with families involved with the child welfare system, the study of workers' perceptions of whether or not they address families' poverty and, if so, how they go about it has not yet been conducted. The study presented begins to address this gap. Analysis from individual interviews with 30 child welfare workers revealed that they differed in their perception of whether or not poverty should be addressed by child welfare and how. Findings suggest workers do what they can despite various barriers, including families' limitations and the fragile US social welfare safety net. Based on the findings, current practice models and policies that impact poverty and child maltreatment reduction are discussed.